Removal of methylene blue contaminant by natural and modified low cost agricultural by-product - Yagub, Musstafa T. A. (Curtin University, 2013)
The study identified an environmentally sustainable agricultural by-product, pine cone and pine leaves, as an effective adsorbent in the removal of methylene blue dye from aqueous solution. Batch studies were made under various operating conditions of pH, initial dye concentration, contact time, salt concentration, agitation speed, adsorbent dosage, and temperature. The kinetics and mechanism of the dye adsorption were obtained. Successful column studies were conducted with pine cone to simulate actual water treatment systems.